The Perception of Time Is Underestimated in Adolescents With Anorexia Nervosa - Vicario, Carmelo M.; Felmingham, Kim (Frontiers in Psychiatry, 2018)
Research has revealed reduced temporal discounting (i.e., increased capacity to delay reward) and altered interoceptive awareness in Anorexia Nervosa (AN). In line with the research linking temporal underestimation with a reduced tendency to devalue a reward and reduced interoceptive awareness, we tested the hypothesis that time duration might be underestimated in AN. Our findings revealed that patients with AN displayed lower timing accuracy in the form of timing underestimation compared to controls. These results were not predicted by clinical, demographic factors, attention and Working Memory performance of the participants. The evidence of a temporal underestimation bias in AN might be clinically relevant to explain their abnormal motivation in pursuing a long term restrictive diet, in line with the evidence that increasing the subjective temporal proximity of remote future goals can boost motivation and the actual behavior to reach them.